miRNA-200a suppresses GNAI1 and PLCB4 to modulate skin pigmentation in cashmere goats - Jianping Li; Baoyu Zhang; Runlai Liu; Xinyu Li; Xuezhao Sun; Qiaoling Zhang (Scientific Reports)
Abstract Coat colour formation in mammals is influenced by melanogenesis and pigmentation processes regulated by miRNAs, including miRNA-200a. Although miRNA-200a is differentially expressed in the skin of cashmere goats with varying coat colours, its regulatory mechanism remains unclear. In this study, miRNA-200a target genes were predicted using miRBase and TargetScan, identifying GNAI1 and PLCB4 as the target genes through GO and KEGG analyses. Dual-luciferase assays using wild-type and mutant plasmids confirmed a direct interaction between miRNA-200a and the 3’UTR regions of these genes. RT-qPCR and Western blot analyses demonstrated that the expression levels of miRNA-200a and its target genes differed significantly between black and white goat skin. In HaCaT cells, transfection with miRNA-200a mimics or inhibitors altered GNAI1 and PLCB4 expression at both mRNA and protein levels. To validate these findings in vivo, subcutaneous injection of antagomiR-200a into BALB/c mice significantly reduced melanin content (P < 0.01) and increased the expression of GNAI1 and PLCB4. These results indicate that miRNA-200a modulates skin pigmentation by suppressing GNAI1 and PLCB4, thereby influencing coat colour in cashmere goats. This study provides a foundational understanding for leveraging genetic regulation to enhance coat colour diversity and develop naturally pigmented breeds.